Detailed DARPP-32 expression profiles in postmortem brains from patients with schizophrenia : an immunohistochemical study - Kunii, Yasuto; Ikemoto, Keiko; Wada, Akira; Yang, Qiaohui; Kusakabe, Takashi; Suzuki, Toshimitsu; Niwa, Shin-ichi (Medical molecular morphology, 2011)
The prevalence of dopamine and cAMP-regulated phosphoprotein 32kD (DARPP-32) is associated with the pathogenesis of schizophrenia. To date, the findings on DARPP-32 cellular expression and distribution in postmortem brains from patients with schizophrenia have been inconsistent. To clarify the detailed cellular expression of DARPP-32 in patients with schizophrenia, we immunohistochemically stained sections from postmortem brains using specific antibodies. We measured the density of immunopositive cells in various brain regions including the prefrontal cortex and compared the data from nine schizophrenia subjects with those of nine age- and sex-matched control subjects. The density of DARPP-32-immunoreactive (IR) neurons was significantly lower in layers II-V of the dorsolateral prefrontal cortex (DLPFC) from subjects with schizophrenia. In contrast, there were no marked differences in DARPP-32 expression in other brain regions. In addition, the density of threonine (Thr34)-phosphorylated DARPP-32-IR neurons was significantly higher in layer V of DLPFC from subjects with schizophrenia. These results suggest that the decrease in DARPP-32 in schizophrenia was more marked in neurons of DLPFC than in other cells or other brain regions, and that this decrease might be partly compensated for by an increase in expression of Thr34-phosphorylated DARPP-32 in DLPFC.